Kostní postižení v uroonkologii. Postavení klodronátu (BonefosR) - Matoušková, M (Česká urologie, 2011)
Metastatic bone disease accompanies malignant tumors in urology with a high prevalence. Bisphosphonates are the choice of the treatment in the frame of complex oncology approaches. We present our experiencies with fifteen years application of clodronate to patients with urologic malignancies.